Communicating information on cardiopulmonary resuscitation to hospitalised patients - Sivakumar, R. (Journal of medical ethics, 2004)
Aim: The primary aim of the study was to evaluate two different methods of communicating information on cardiopulmonary resuscitation (CPR) to patients admitted to general medical and elderly care wards. The information was either in the form of a detailed information leaflet (appendix I) or a summary document (appendix II). The study examined the willingness of patients in seeking detailed information on cardiopulmonary issues. Setting: The study was conducted over three months on a general medical ward and an acute elderly care ward in two district general hospitals. Methods: A detailed information leaflet on CPR was provided to the nursing staff on the wards. An A4 summary document summarising the CPR decision making process and basic information on cardiopulmonary issues was placed in a folder at the foot of each bed on the elderly care ward. On the general medical ward it was displayed prominently over the head of all beds. Results: Out of the 274 patients admitted to the general medical ward only two requests were received for the detailed information leaflet. On the elderly care ward there were 182 admissions but no patients or their relatives requested the leaflet. Conclusions: Availability of basic information on cardiopulmonary resuscitation to all patients is practical and does not lead to unnecessary distress or offence to patients or their carers. It makes the decision making process more transparent. Detailed information leaflets are of value for a minority of hospitalised patients.